Pengaruh Halal Lifestyle dan Product Bundling Terhadap Minat Beli Ulang dengan Mediasi Keputusan Pembelian Pada Produk Skincare Halal - Ummah, Halizah Faridatul; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2024)
The existence of a product bundling strategy and the necessity of implementing a halal lifestyle in Islam are things that must be considered when purchasing a product. The aim of this research is to analyze the influence of halal lifestyle and product bundling on repurchase intention by mediating purchasing decisions on halal skincare product. The research method uses quantitative methods using purposive sampling technique with a total of 133 respondents who were analyzed using SEM-PLS 4.0. The results of this research show that halal lifestyle and product bundling influence purchasing decisions, halal lifestyle and product bundling influence repurchase intention with decision mediation purchase. The result of this study are used as an appeal, especially for Muslim communities, to be more careful and not be tempted by cheap prices before buying halal skincare products. And this study can be used as literature related to halal lifestyle and product bundling on repurchase interest with purchasing decision mediation.